Manajemen FOMO: Analisis Kritis atas Buku Fear of Missing Out Karya Patrick J. McGinnis - Aprilyanti, Siva; Asbari, Masduki; Supriyanti, Alfiana (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to present a review of a book with critical reading entitled Fear of Missing Out by Patrick J. McGINNIS. Descriptive qualitative research methods were used to analyze the contents of the book. The study results show that this book provides valuable insight into the psychological and social implications of the fear of being left behind, offering readers a deeper understanding of this modern phenomenon and empowering them to navigate the challenges it poses. This book serves as a guide for individuals who want to overcome the fear of falling behind and foster a healthier relationship with technology, social media, and their own sense of self-worth.